Evaluation of HLA-DQ2/DQ8 genotype in patients with celiac disease hospitalised in 2012 at the Department of Paediatrics - Szałowska-Woźniak, Dorota A.; Bąk-Romaniszyn, Leokadia; Cywińska-Bernas, Agnieszka; Zeman, Krzysztof (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Celiac disease (CD) is a permanent intolerance to gluten that occurs in genetically predisposed individuals and leads to small intestinal mucosa damage. According to ESPGHAN guidelines from 2012, CD can be diagnosed in a patient with characteristic clinical symptoms, in whom, anti-tissue transglutaminase antibodies (> 10 times the upper limit) are found, endomysial antibodies (EMA) is confirmed and a positive genetic test is obtained. In these conditions no small-bowel biopsies are required. Aim : Evaluation of the presence of HLA-DQ2 and HLA-DQ8 haplotypes in children with previously diagnosed CD, hospitalised in 2012 at the Department of Paediatrics and Immunology and/or the Gastroenterological Outpatient Clinic, and their relatives. Material and methods : Blood samples of 22 subjects, including 9 children with CD diagnosed on the basis of clinical symptoms, serological investigations and small-intestine biopsy, 7 diagnosed on the basis of clinical symptoms and serological investigations, 2 with the suspicion of CD on the basis of clinical symptoms and 4 relatives of a child with CD. Methods: HLA-DQ2/DQ8 test, automatic evaluation by EUROArrayScan. Results : The presence of HLA-DQ2 and/or HLA-DQ8 genotype was confirmed in 16 children with CD diagnosed on the basis of clinical symptoms and serological tests with/without intestinal biopsy, in 2 with the suspicion of CD and in 1 relative of a celiac child. Conclusions : The evaluation of HLA-DQ2/DQ8 haplotype confirms the genetic predisposition to CD in subjects with the disease diagnosed previously on the basis of clinical symptoms, serological tests or intestinal biopsy. Genetic testing is particularly indicated for the diagnosis of CD in infants consuming gluten for a short time and in small amounts.